JDHASA 2023
DOI: 10.55492/dhasa.v4i01.4440
|View full text |Cite
|
Sign up to set email alerts
|

An overview of Sesotho BLARK content

Abstract: This article overviews digital language resources available for Sesotho, an official language of South Africa. The South African Center for Digital Language Resources (SADiLaR) repository is used as a reference as it is the official host of various language resources for South African languages. A total of 18 written resources are identified from the repository, and a further 16 spoken resources are identified. Finally, a total of 45 applications and modules were identified. Findings indicate that the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Digital language resources and human language technologies audits for South African languages indicate that all indigenous languages of South Africa are under-resourced (Grover et al, 2010(Grover et al, , 2011Barnard et al, 2014;Moors et al, 2018a,b). More specifically, Sibeko and Setaka (2022) reviewed the basic language resource kit for Sesotho and concluded that many necessary digital language resources are still lacking.…”
Section: Related Workmentioning
confidence: 99%
“…Digital language resources and human language technologies audits for South African languages indicate that all indigenous languages of South Africa are under-resourced (Grover et al, 2010(Grover et al, , 2011Barnard et al, 2014;Moors et al, 2018a,b). More specifically, Sibeko and Setaka (2022) reviewed the basic language resource kit for Sesotho and concluded that many necessary digital language resources are still lacking.…”
Section: Related Workmentioning
confidence: 99%
“…Sesotho is used by more than ten million speakers in a few countries in Southern Africa including South Africa, Lesotho, and Zimbabwe (Marupi and Charamba, 2022;Sibeko and Setaka, 2022). In fact, it is one of the official languages in Lesotho, Zimbabwe, and South Africa.…”
Section: Contextualising Sesothomentioning
confidence: 99%
“…It is also used for media, political, religious, and other uses. Even so, a recent investigation of the Sesotho Basic Language Resource Kit (BLARK) content has revealed that there is a severe shortage of digital language resources available for Sesotho (Sibeko and Setaka, 2022). As such, Sesotho remains a low-resourced language (Roux and Bosch, 2019;Sibeko and Setaka, 2022).…”
Section: Contextualising Sesothomentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation into text readability levels has been a subject of scholarly examination spanning over a century (De Clercq & Hoste 2016, Zamanian & Heydari 2012. However, there remains a notable dearth of research pertaining to text readability in African indigenous languages (Sibeko & De Clercq 2023, Sibeko & Van Zaanen 2021. To put it simply, readability pertains to the ease with which a given text can be read (Dahl 2004).…”
Section: Introductionmentioning
confidence: 99%